PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP MINAT BELI ULANG BANDENG JUWANA VACCUM MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PELANGGAN PT. BANDENG JUWANA ELRINA SEMARANG) - Mahyarani Tiara Ghassani; Sri Suryoko (Universitas Diponegoro, 2017)
Culinary business is one of businesses that keep growing in Semarang. With the large amount of natural resources, that is ikan bandeng (milkfish), causing culinary business named bandeng duri lunak (milkfish with soft bone) more popular. PT. Bandeng Juwana Elrina is one of food business that made ikan bandeng as their basic material to create a special food from Semarang. From the sales data of Bandeng Juwana Vaccum (kg) in year 2014 to 2016, it happened to fluctuated, or the sale is not steady from time to time.The purpose of this research is to find out about the influences of the quality and the price of the product to the willingness of people to buy the product repeatedly through the satisfaction of the buyers of PT. Bandeng Juwana Elrina in Semarang. The type of research that used for this research is explanatory research, and there are 100 samples. Sampling technique that used for this research is purposive sampling and accidental sampling. The techniques of the data collection are the study of library, questionnaire, and interview. The techniques of the data analysis are through cross-tabulation test, correlation test, determination test, simple linear regression test, t test, F test, and sobel test by A.F. Hayes with the help of IBM SPSS (Statistical Product and Service Solutions) program version 22.0.The results of this research showed that there is a positive influence between the quality and price of the product on customer satisfaction partially and simultaneously. The results also indicate that there is a positive influence between product quality and price on repurchase intention partially and simultaneous. Based on the results of the analysis of sobel test, it is known that the variable of customer satisfaction is the partial mediation variable that is able to mediate the effect of product quality on repurchase intention with Z value equal to 3,2611 bigger than t table (1,9845) and p value equal to 0,0011 bigger from 0.05. Meanwhile, the variable of consumer satisfaction is the full mediation variable that is able to mediate the influence of price on repurchase intention with the value of Z equal to 2,7835 bigger than t table (1,9845) and the value of p equal to 0.0054 is greater than 0.05. The advice given is to maintain the good quality of the product and observe the prices that are considered more expensive compared to other brands in order to boost up the repurchase intention.